Impact of edutainment on heritage sites : a case study of Haw Par Villa (Singapore) - Lin, Cyndy Xinyi (2013)
Visitor attractions of the new age are gradually adopting edutainment modes to inject interaction and excitement together with learning. This explains the growing presence of heritage theme parks and interactive history museums. Even in Singapore, edutainment modes are widely adopted in visitor attractions such as the Singapore Science Centre as well as KidZania. These edutainment modes have proven to be successful and popular among children. However, the use of edutainment modes in Singapore’s heritage sites has not been explored yet. Therefore, this study aims to uncover the effectiveness of implementing edutainment modes in heritage sites to provide a meaningful experience for visitors. The heritage site chosen for edutainment modes to be studied in this report is Haw Par Villa (HPV). HPV is a visitor attraction that seeks to narrate Chinese mythological stories as well as Chinese cultural values. Its unique past as well as ambiguous future were the motivating factors for this study.